Search for single production of a vectorlike T quark decaying into a Higgs boson and top quark with fully hadronic final states using the ATLAS detector - Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review, 2022)
A search is made for a vectorlike T quark decaying into a Higgs boson and a top quark in 13 TeV proton-proton collisions using the ATLAS detector at the Large Hadron Collider with a data sample corresponding to an integrated luminosity of 139 fb−1. The Higgs-boson and top-quark candidates are identified in the all-hadronic decay mode, where H→b¯b and t→bW→bq¯q′ are reconstructed as large-radius jets. The candidate Higgs boson, top quark, and associated B hadrons are identified using tagging algorithms. No significant excess is observed above the background, so limits are set on the production cross section of a singlet T quark at 95% confidence level, depending on the mass mT and coupling κT of the vectorlike T quark to Standard Model particles. In the considered mass range between 1.0 and 2.3 TeV, the upper limit on the allowed coupling values increases with mT from a minimum value of 0.35 for 1.07<mT<1.4 TeV to 1.6 for mT=2.3 TeV.